Legal Status of Climate Refugees: Is it Regulated in International Law? - Wattiheluw, Azmi Julifa; Anwar, Arman; Tuhulele, Popi (Uti Possidetis: Journal of International Law, 2024)
This paper analyses the phenomenon of climate refugees, people who migrate due to climate crisis in their home country and the determination of their legal status, rights, and protection within the international law legal framework. International law defines refugees as someone who is forced to leave their country due to persecution, war, or violence. Refugees have a well-founded fear of persecution because of race, religion, nationality, political opinion, or membership in a particular social group. The presence of climate refugees encourages an additional priority for those who are forced to leave their home country due to the climate crisis. This paper uses the normative legal research method to examine the International Law Instruments, books, theses, article, journals, websites, legal dictionaries, and encyclopedias, which are collected through normative qualitative legal analysis. The paper finds that there are several international legal arrangements that may provide protections for the climate refugees based on the context of human rights, where the climate refugees legal status are equalised as the refugees defined in the 1951 Refugee Convention.